Maggots and wound healing: the effects of Lucilia sericata larval secretions upon interactions between human dermal fibroblasts and extracellular matrix proteins - Horobin, Adele Jayne (2005)
The introduction of necrophagous fly larvae (maggots) into chronic wounds for the purpose of inducing healing is an ancient practice that has recently undergone a renaissance in Western medicine. Through clinical observations, maggots are broadly recognised to debride the wound of necrotic tissue, cleanse the wound of infection and promote granulation tissue formation. Despite such recognition, little research at the biological level has been undertaken to identify the mechanisms by which maggots accomplish such feats.